Evaluasi Hasil, Akibat, dan Dampak Pelaksanaan Program Pengembangan Irigasi Desa : Studi Kasus Kabupaten Sleman Propinsi D.I. Yogyakarta - Suprodjo Pusposutardjo; Wisnu Wardana (agriTECH, 1997)
Evaluation study on the result, effect and the impact of crash program on farmers managed irrigation system (FMIS) improvement was conducted in several irrigation schemes of Sleman District, Yogyakarta Special Territory. Indicators of the result, effect and the impact of improvement were determined based on the scope of dimensions of FMIS which theoreticaly covers autonomy, natural characteristics, and technology dimensions. Considering that management performance of irrigation system is a resultant attribute of structures and management performances, the fuzzy set theory was chosen to analyze the contribution of qualitative parameters of management element. These management elements related to the scope of autonomy and natural characteristic dimensions of FMIS. Result of study indicated that the result, effect and the impact of the FMIS improvement project was locally specifics, could not he generalized without taking into account the similarities of the local condition. Significant impact on agricultural improvement was not recorded because farmers in the sample study had been practicing an intensive farming. Moreover, the available water and land resources had fully utilized. The impact of FMIS improvement project on management capability of water user organization was also not significant because the betterment of irrigation structures as the element of system was relatively small.